ChemInform Abstract: Thermal Expansion and Phase Transitions of α‐AlF3. Issue 44 (4th November 2014) - Morelock, Cody R.; Hancock, Justin C.; Wilkinson, Angus P.
Abstract α‐AlF3 is prepared by thermal treatment of anhydrous AlF3 (Ni tube in evacuated quartz ampoule, 1338 K, 72 h).